FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETIDAKPATUHAN KUNJUNGAN KEHAMILAN K1-K4 PADA IBU HAMIL DI BPM BIDAN MARI SENTONO, PEGADUNGAN, KALIDERES TAHUN 2020 - Santi Fatmawati; Gisely Vionalita; Rini Handayani; Devi Angeliana Kusumaningtiar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
One of the causes of Maternal Mortality Rate (MMR) is complications in pregnancy and childbirth. Complications of pregnancy and childbirth can be prevented by regular antenatal care (ANC) examinations. ANC is a visit by pregnant women with health workers to get pregnancy services in accordance with established standards. Of these 114 pregnant women patients, there were patients who were not compliant (having visits less than 4 times) as many as 89 (78%) patients while the data on the coverage of antenatal care visits in DKI Jakarta in 2019 was 88.54%, this was due to a lack of knowledge about pregnancy visits, parity, and mileage. The purpose of this study was to determine the factors associated with non-adherence to pregnancy visits K1-K4 in pregnant women. This research is a quantitative research with a cross sectional design. This research was conducted in January – August 2021. The population in this study were all pregnant women at BPM Midwife Mari Sentono in 2021 as many as 114 people in January – April. The sample in this study was 75 medical records of pregnant women with simple random sampling method. Data analysis was carried out univariate and bivariate with Chi Square test (α = 0.05) and calculate the Prevalence Ratio (PR) value. The results of the Chi Square test are age (p-value = 0.962, PR = 1.085), education (p-value = 0.027, PR = 0.487), occupation (p-value = 1,000, PR = 1,000), parity (p-value = 1,000). value = 0.037, PR = 1.975), and distance traveled (p-value = 0.024, PR = 2,000), the conclusion is that there is a relationship between education, parity and distance traveled with non-compliance with K1-K4 visits to pregnant women at BPM Midwife Mari Sentono. Suggestions for the BPM are expected to be used as input to develop a special program in increasing the coverage of ANC visits during the pandemic in order to minimize the incidence of maternal and infant mortality.